The Relation of Maxim Flouting Used to Illocutionary Function of Politeness in 12 Years a Slave Movie - Zain Nabilah Anjani; Jepri Jepri; Siti Hafsah (Prologue: Journal on Language and Literature, 2020)
This research explores types of maxim flouting in 12 Years A Slave’s Movie and aims to identify the types of maxim flouting in 12 Years A Slave movie and to seek out the relation of maxim flouting to the illocutionary function of politeness. The pragmatic analysis using H. P. Grice’s theory of maxim flouting is used with descriptive methodology. The movie scripts were taken as the primary data. Researcher found that there are four types of maxim flouting performed by Solomon Northup; and the relation of maxim flouting to the illocutionary function of politeness are competitive, collaborative, convivial, and conflictive.